Chemical composition of essential oil and anti trichomonas activity of leaf, stem, and flower of Rheum ribes L. extracts - Forough Naemi; Gholamreza Asghari; Hossein Yousofi; Hossein Ali Yousefi (Mashhad University of Medical Sciences, 2014)
Objectives: Trichomoniasis is one of the most common sexually transmitted diseases in humans and is caused by the protozoan Trichomonas vaginalis. Nowadays, increasing resistance to drugs such as metronidazole resulted in many problem, so new effective remedies are needed. In this study, we evaluate constituents of essential oil and anti-trichomonas activity of Rheum ribes. Materials and Methods: The essential oil from Rheum ribes L.flower growing wild in Iran was analyzed by GC/MS. The parasites were treated with different extract and fractions of the flower, stem, and leave of the plant. Anti-trichomonas activity was evaluated using an in vitro assay.   Results: In all, 19 compounds were identified; palmitic acid [27.08%], n-eicosane [9.9%], n-tetracosane [7.34%], linoleic acid [6.56%], and ethyl linoleate [4.76%] were the main components of the oil. Rheum ribes extracts and fractions concentration dependently inhibited the ability of parasites to growth. This was associated with polarity of solvent used for fractionation and plant parts used for extraction. Conclusion: Findings demonstrate the potential of Rheum ribes extracts as an anti-trichomonas agent for human use. Further studies are required to evaluate its toxicity and safety.